Pengembangan Media Pembelajaran Berbasis Multimedia Interaktif Pada Materi Desain Jaringan Lokal (LAN) Dengan Model Pembelajaran Problem Based Learning (Studi Kasus : DI SMK Negeri 3 Malang) - Kurnila Putri Islamawati; Satrio Hadi Wijoyo; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Interactive learning media is a learning tool that can be used to convey learning content interestingly by adding a learning model that empowers students to think critically about a problem and identify problems. However, at State Vocational High School 3 in Malang, the media used for learning activities uses only power points and material descriptions with lectures and questions, making learning less effective and less interesting. This trend also reduces the learning achievements of the students. Based on these issues, researchers want to develop interactive multimedia learning media using problem-based learning (PBL) learning models to promote a lively classroom atmosphere, which also increases the quality of students learning outcomes. The development model used is ADDIE with stages (1) analysis; (2) design; (3) development; (4) implementation; (5) evaluation. The media has been validated by media experts and material experts to determine the feasibility of testing. The study was conducted on TKJ 2 grade 10 students in SMKN 3 Malang, which corresponded to 37 students. The results of the study show: (1) Creating Adobe Flash CS6-based learning media for computer topics and basic networks. (2) The results of the evaluation of several experts: (a) media expert I and media expert II, both with 78.7% and in the category good. (b) Results of the Evaluation of Materials Expert I and Material Experts II, both 92% and 91% in the Excellent category. (3) Preliminary test results 29.8% of the students had completed. after students get treatment with learning media, the test showed that 83.8% of the students had completed the standard given by the school, so the use of Interactive Multimedia had an impact on student learning.